Heat equation with a general stochastic measure in a bounded domain - Boris Manikin (Modern Stochastics: Theory and Applications)
A stochastic heat equation on $[0,T]× B$, where B is a bounded domain, is considered. The equation is driven by a general stochastic measure, for which only σ-additivity in probability is assumed. The existence, uniqueness and Hölder regularity of the solution are proved.